Hubungan Karakteristik Penduduk dengan Perilaku Buang Air Besar Sembarangan (BABS) di Desa Silo Lama Tahun 2022 - Imam Yazid; Ririn Oktaviani; Salsabila Nailul Muna Lubis; Dea Amalia Putri; Nisya Rahmaini Marpaung (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
One of the public health problems that is still a global problem is the habit of open defecation. The habit of open defecation (BABS) is one example of a very bad and unhealthy habit. The purpose of this study was to determine the description and relationship between the dependent and independent variables. This research is a quantitative research with a cross sectional research design. The total population in this study were all residents of the Silo Lama village, Silau Laut sub-district with a total of 1264 families and the sample in the study was 125 families in Silo Lama Village, Silau Laut District. Procedures for collecting data were interviews and questionnaires, data analysis was carried out univariate and bivariate with the help of the SPSS program. The results showed that age and open defecation behavior did not have a relationship with p = 0.695 (> 0.05), and the variables associated with open defecation were education, knowledge, attitudes, and habits. It is better if the community in Silo Lama village, Silau Laut sub-district, should conduct a village consultation regarding open defecation in order to obtain a solution that will be carried out to deal with these health problems.